Preparation method and application of spherical nano SiOx material
By controlling the amount of water in a hydrogen-heated plasma, spherical nano SiOx with controllable oxygen content is solved, and the problem of difficult control of SiOx oxygen content is improved, the electrochemical performance is simplified and the preparation process is simplified.
Patent Information
- Application Number
- CN202510035993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The oxygen content in SiOx is difficult to control, affecting its electrochemical performance. The existing premagnetization and prelithiation modification methods increase the preparation steps and costs, and pose safety risks.
The hydrogen-heated plasma is used to generate spherical nano SiOx at one time. By controlling the amount of water introduced, the oxygen content in SiOx is controllable, and the generated material is applied to the negative electrode material of lithium-ion battery.
The controllability of the oxygen content in SiOx is achieved, the electrochemical performance is improved, the preparation steps are simplified, the cost is reduced, and safety hazards are avoided.
Smart Images

Figure CN119822375A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery negative electrode materials and relates to a preparation method and application of a spherical nano-SiOx material. Background Art
[0002] With the widespread application of lithium-ion batteries in portable electronic products, electric vehicles and other fields, traditional graphite negative electrode materials have been unable to meet people's demand for high-energy-density lithium-ion batteries. Silicon-based negative electrode materials have the advantages of abundant reserves and high capacity, and are considered to be one of the most promising next-generation lithium-ion battery negative electrode materials. Silicon negative electrode material is an alloy-based lithium storage negative electrode material, which has attracted widespread attention due to its extremely high theoretical specific capacity. In addition, silicon has abundant reserves, low preparation costs, and is environmentally friendly. However, silicon will produce a large volume change during the lithium insertion / extraction process, causing damage to the electrode structure and the continuous formation of a solid electrolyte membrane (SEI), resulting in poor cycle stability of silicon-based negative electrodes and low first coulombic efficiency. Problems, greatly limiting the industrial application of silicon-based negative electrodes.
[0003] SiOx has attracted much attention as a modified silicon-based negative electrode material with high specific capacity (2615mAh / g) and excellent stability. Its high stability is mainly due to the fact that SiOx will generate lithium silicate and lithium oxide in situ when it is first embedded with lithium, thereby protecting the internal silicon-lithium alloy. However, the generation of lithium silicate and lithium oxide will irreversibly consume a large amount of lithium ions, causing a decrease in the first coulombic efficiency. At present, many scholars at home and abroad mainly use the strategies of pre-magnesiumization and pre-lithiation to modify silicon-oxygen negative electrode materials, thereby improving the first coulombic efficiency.
[0004] For example, patent CN118899428A discloses a method for preparing a pre-magnesium silicon oxide negative electrode material, wherein silicon oxide, a magnesium source and a carbon source are weighed according to a mass ratio, placed in a mortar, ground and mixed to obtain a precursor; the precursor is placed on a carrier of a Joule heating device, and under a protective atmosphere, the power supply of the electrode in the Joule heat treatment device is turned on, and the precursor is subjected to a thermal shock treatment to obtain a silicon negative electrode material with high initial efficiency and gram capacity;
[0005] Patent CN118373427A discloses a method for preparing a pre-magnesium silicon oxide negative electrode material, which comprises mixing silicon and magnesium oxide to obtain a first mixed material; vacuum heating and heat preservation of the first mixed material, and obtaining a magnesium-embedded silicon oxide material after cooling; crushing the magnesium-embedded silicon oxide material and placing it in a reaction vessel, heating it at a temperature of 600 to 950° C. and heat preservation for 1 to 20 hours, and obtaining a magnesium-containing silicon oxide material after cooling; heating the magnesium-containing silicon oxide material under the protection of an inert atmosphere, and coating the surface of the magnesium-containing silicon oxide material with a carbon source gas to form a coating layer, and obtaining a pre-magnesium silicon oxide negative electrode material.
[0006] Patent CN118693258A discloses a method for preparing a silicon oxide negative electrode material, comprising mixing an organic carbon source with an organic solvent, stirring and dissolving the mixture to obtain a mixed solution; mixing the mixed solution, silicon oxide and metal powder, stirring and then allowing the mixture to stand; sintering the material after standing in an inert gas to obtain a sintered material; mixing the sintered material, a solvent and an acid, stirring, and drying after solid-liquid separation; mixing the dried material, a high molecular polymer, an organic solvent and a conductive agent, stirring, and heating the mixture by microwave in an inert gas to obtain the silicon oxide negative electrode material.
[0007] Although the effects of oxygen can be reduced and the first coulombic efficiency of SiOx can be improved by pre-magnesiation and pre-lithiation, there are the following problems: 1) The preparation steps and costs are significantly increased, and the more steps there are, the easier it is to introduce impurities; 2) Magnesium and lithium have high reactivity and there is a certain risk. Therefore, it is more effective to appropriately reduce the oxygen content of SiOx to reduce the irreversible consumption of lithium ions when lithium silicate and lithium oxide are generated, but it does not affect the protective effect of lithium silicate and lithium oxide. However, the current method for preparing SiOx is difficult to control the oxygen content of SiOx: 1) If it is prepared by oxidation of Si, it is very easy to generate a large amount of SiO2 and the distribution of Si and O is uneven, so the electrochemical performance is reduced; 2) If it is prepared by reducing SiO2 with carbon or active metals, it is easier to generate Si. Therefore, it is necessary to find a new method for preparing SiOx. Summary of the invention
[0008] Aiming at the technical problem that the oxygen content in SiOx is difficult to control, the present invention provides a method for preparing a spherical nano-SiOx material. The method adopts hydrogen thermal plasma to generate spherical nano-SiOx at one time. The oxygen content in SiOx is controllable by controlling the amount of water introduced. The obtained material is applied to the negative electrode material of a lithium ion battery and has excellent electrochemical performance.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] The present invention provides a method for preparing a spherical nano-SiOx material, comprising the following steps:
[0011] 1) Produce a stable hydrogen thermal plasma arc;
[0012] 2) Adding a silicon source to the hydrogen thermal plasma arc, the silicon source is cracked and reacted to generate silicon vapor;
[0013] 3) Water is introduced into the hydrogen thermal plasma arc through the carrier gas, and the water is rapidly vaporized into water vapor and evenly mixed with silicon vapor, and then the two react to form spherical nano-SiOx.
[0014] In the above technical solution, the silicon source is one of silicon tetrahydride, monochlorosilane, dichlorosilane, trichlorosilane or silicon tetrachloride.
[0015] In the above technical solution, the water in step 3) is atomized water.
[0016] In the above technical solution, the molar ratio of the silicon source to water is 1:0.1-10.
[0017] The present invention also provides application of the spherical nano-SiOx material prepared by the preparation method as a negative electrode material for lithium-ion batteries.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The invention adopts hydrogen thermal plasma to generate spherical nano-SiOx at one time, with a sphericity rate of ≥80%, a particle size D90 of <200nm, a narrow particle size distribution, good dispersibility, and not easy to agglomerate, and Si and O are evenly distributed, and Si is completely coated; the invention controls the amount of introduced water so that the oxygen content in SiOx is controllable, the oxygen content is between 0 and 53.33wt.%, and the electrochemical performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope photograph of the spherical nano-SiOx material obtained in Example 6.
[0021] Figure 2 This is the X-ray diffraction pattern of the spherical nano-SiOx material obtained in Example 6.
[0022] Figure 3 This is the particle size distribution of the spherical nano-SiOx material obtained in Example 6.
[0023] Figure 4 This is a transmission electron microscope image of the spherical nano-SiOx material obtained in Example 6.
[0024] Figure 5 The cyclic test results of the battery assembled with the spherical nano-SiOx material obtained in Example 6 at a current density of 200 mA / g. DETAILED DESCRIPTION
[0025] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.
[0026] The thermal plasma generator used in the following embodiments is a radio frequency inductively coupled thermal plasma with a power of 36Kw.
[0027] Example 1
[0028] (1) Produce stable hydrogen thermal plasma:
[0029] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0030] (2) Preparation of spherical nano-SiOx materials:
[0031] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:1, and then the two react to generate spherical nano-SiOx.
[0032] Example 2
[0033] (1) Produce stable hydrogen thermal plasma:
[0034] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0035] (2) Preparation of spherical nano-SiOx materials:
[0036] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:2, and then the two react to generate spherical nano-SiOx.
[0037] Example 3
[0038] (1) Produce stable hydrogen thermal plasma:
[0039] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0040] (2) Preparation of spherical nano-SiOx materials:
[0041] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:3, and then the two react to generate spherical nano-SiOx.
[0042] Example 4
[0043] (1) Produce stable hydrogen thermal plasma:
[0044] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0045] (2) Preparation of spherical nano-SiOx materials:
[0046] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:4, and then the two react to generate spherical nano-SiOx.
[0047] Example 5
[0048] (1) Produce stable hydrogen thermal plasma:
[0049] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0050] (2) Preparation of spherical nano-SiOx materials:
[0051] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:5, and then the two react to generate spherical nano-SiOx.
[0052] Example 6
[0053] (1) Produce stable hydrogen thermal plasma:
[0054] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0055] (2) Preparation of spherical nano-SiOx materials:
[0056] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:6, and then the two react to generate spherical nano-SiOx.
[0057] The morphology of the spherical nano-SiOx material obtained under the above conditions was examined using a Japanese electron scanning electron microscope (JSM-7001F). Figure 1 As shown, it can be seen that SiOx is a spherical particle with a diameter between 100-200nm; the particle surface is smooth and has good dispersibility.
[0058] The composition of the spherical nano-SiOx material obtained under the above conditions was detected by Philips X-ray powder diffractometer (X'Pert PRO MPD). The results are as follows: Figure 2 As shown, it can be seen that SiOx has both sharp diffraction peaks belonging to crystalline Si and broad diffraction peaks belonging to amorphous SiOx.
[0059] The particle size of the spherical nano-SiOx material obtained under the above conditions was measured using a BeNano 90 particle size potential analyzer. The results are as follows: Figure 3 As shown, it can be seen that the particle size distribution of SiOx is narrow, with D50 of about 120nm and D90 of about 200nm.
[0060] The morphology and structure of the spherical nano-SiOx materials obtained under the above conditions were examined using a Japan Electron Transmission Electron Microscope (JEM-21001F). Figure 4 As shown in Figure 2, it can be seen that SiOx is dense inside and smooth on the surface; Si and O are evenly distributed, and no obvious boundary is observed.
[0061] Example 7
[0062] (1) Produce stable hydrogen thermal plasma:
[0063] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0064] (2) Preparation of spherical nano-SiOx materials:
[0065] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:7, and then the two react to generate spherical nano-SiOx.
[0066] Example 8
[0067] (1) Produce stable hydrogen thermal plasma:
[0068] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0069] (2) Preparation of spherical nano-SiOx materials:
[0070] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:8, and then the two react to generate spherical nano-SiOx.
[0071] Example 9
[0072] (1) Produce stable hydrogen thermal plasma:
[0073] The thermal plasma generator generates stable argon thermal plasma; hydrogen is added through the edge gas and quenching gas, and the amount of hydrogen added is 1000L / h, generating a stable hydrogen thermal plasma.
[0074] (2) Preparation of spherical nano-SiOx materials:
[0075] Silicon tetrachloride is added to the hydrogen thermal plasma arc, and the silicon tetrachloride cracks and reacts to generate silicon vapor. Water is atomized using an atomizer, and the atomized water is added to the plasma arc through a carrier gas. The water is quickly vaporized into water vapor and evenly mixed with the silicon vapor. The silicon / water molar ratio is controlled to be 1:9, and then the two react to generate spherical nano-SiOx.
[0076] The oxygen content of the spherical nano-SiOx materials obtained in Examples 1 to 9 was detected by an oxygen, nitrogen and hydrogen analyzer (ONH836), and the results are shown in Table 1. It can be seen that the oxygen content of SiOx can be well controlled by the method of the present invention, and the oxygen content is positively correlated with the amount of water added.
[0077] The spherical nano-SiOx materials prepared in Examples 1 to 9 were mixed with acetylene black and CMCLi-A (binder) at a mass ratio of 6:2:2 to form a slurry, and evenly coated on a copper foil current collector to obtain an electrode sheet. Metal lithium was used as the counter electrode, a polypropylene microporous membrane was used as a diaphragm, and 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as an electrolyte. A button battery was assembled in an argon-protected glove box, and a charge and discharge test was performed. The test current density was 200 mA / g, and the charge and discharge voltage range was 0.01 to 3.0 V. The battery test results are shown in Table 1. Conventional SiO negative electrode materials were used as controls.
[0078] Figure 5The cyclic test results of the battery assembled with the spherical nano-SiOx material obtained in Example 6 at a current density of 200 mA / g.
[0079] Table 1 Oxygen content in SiOx materials and battery performance test results
[0080]
[0081] As can be seen from Table 1, by controlling the silicon / water molar ratio, nano-SiOx particle materials with different oxygen contents and electrochemical properties can be prepared; the oxygen content of nano-SiOx is inversely proportional to its first reversible specific capacity and first coulombic efficiency, and is proportional to the capacity retention rate. Compared with conventional SiOx, due to the reduction in oxygen content, the capacity and first coulombic efficiency of spherical nano-SiOx have been significantly improved, and it also has a better capacity retention rate. It can be seen that the technology has good effect and strong scalability. In addition, compared with the prior art, this method has simple steps, low cost and easy application.
[0082] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. A method for preparing spherical nano-SiOx material, characterized in that: The following steps are involved: 1) Produce a stable hydrogen thermal plasma arc; 2) Add silicon source to the hydrogen thermal plasma arc, the silicon source cracks and reacts to generate silicon vapor; 3) Water is introduced into the hydrogen thermal plasma arc through the carrier gas, and the water is quickly vaporized into water vapor and evenly mixed with silicon vapor, and then the two react to form spherical nano-SiOx.
2. The preparation method according to claim 1, characterized in that: The silicon source is one of silicon tetrahydride, monochlorosilane, dichlorosilane, trichlorosilane or silicon tetrachloride.
3. The preparation method according to claim 1, characterized in that: The water in step 3) is atomized water.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the silicon source to water is 1:0.1-10.
5. Application of the spherical nano-SiOx material prepared by the preparation method according to any one of claims 1 to 4 in negative electrode materials for lithium-ion batteries.